Ferrocene functionalized metal organic framework material and application thereof

By modifying the ferrocene-functional metal organic frame material Fc-NH2-MIL-53 (Al) to the working electrode of the electrochemical sensor, the problem of long time and expensive equipment detection of heavy metal lead in electronic cigarettes in the prior art is solved, and a rapid detection effect with high sensitivity and low cost is achieved.

CN119823399APending Publication Date: 2025-04-15YUNNAN TOBACCO QUALITY SUPERVISION MONITORING STATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411877601.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art when detecting heavy metal lead in electronic cigarettes, the method has high accuracy but is time-consuming, expensive equipment and complex operation, which limits the application of large-scale inspection.

Method used

The working electrode of the electrochemical sensor is modified by Fc-NH2-MIL-53 (Al), a ferrocene-functional metal-organic framework material, and the square wave anode dissolution voltammetry is used to achieve high sensitivity detection of lead ions.

Benefits of technology

It realizes rapid and accurate detection of heavy metal lead, with a detection limit as low as 0.437μg/L, high sensitivity, simple preparation process and low cost, and has wide application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823399A_ABST
    Figure CN119823399A_ABST
Patent Text Reader

Abstract

The invention discloses a ferrocene functionalized metal organic framework material and application thereof, and belongs to the technical field of environment functional materials and application. NH2-MIL-53 (Al) and ferrocenecarboxylic acid are coupled through 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide to form the Fc-NH2-MIL-53 (Al) material, and the prepared Fc-NH2-MIL-53 (Al) material is only composed of C, N, O, Al and Fe and is of a cluster structure formed in a sheet shape. According to the present invention, the Fc-NH2-MIL-53 (Al) is modified on the working electrode of the electrochemical sensor, the Fc-NH2-MIL-53 (Al) is used for specifically detecting the lead ions, the advantages of high sensitivity, low detection limit and the like are represented, the detection limit of the lead ions is as low as 0.437 [mu] g / L, the sensitivity is 0.317 [mu] A / ([mu] g / L), the preparation process is simple, the cost is low, and the significant promotion and application prospects are provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental functionalized materials and applications, and specifically relates to a ferrocene functionalized metal organic framework material and an application thereof. Background Art

[0002] Heavy metal elements are the focus of e-cigarette regulations in various countries. Lead, arsenic, chromium, mercury, nickel, cadmium and antimony are harmful substances that may exist in e-cigarette aerosols. After being inhaled by the human body, they will accumulate in human organs, inactivate certain enzymes in the human body, and cause chronic poisoning, thus affecting human health. The "Mandatory National Standard for Electronic Cigarettes" GB 41700-2022 was officially implemented on October 1, 2022, and detailed requirements were made for the content of safety components such as heavy metals and a large number of additives, marking that China's e-cigarettes have entered the national standard production stage. At present, the detection of heavy metal lead in e-cigarettes at home and abroad mainly uses methods such as inductively coupled plasma mass spectrometry (ICP-MS), synchrotron radiation X-ray spectroscopy (SR-XRF) and flame atomic absorption spectrometry (FAAS). These methods have high precision and low detection limits, and play an irreplaceable role in analyzing trace heavy metals, but they are time-consuming, require specialized technicians, expensive equipment, complex pretreatment and high maintenance costs; therefore, only research institutions or companies that test a large number of samples will use these methods.

[0003] Metal-organic frameworks (MOFs) are porous materials formed by the coordination of inorganic metal ions and organic ligands. During the adsorption of heavy metal ions, the pore structure of MOFs can increase the contact surface between the electrode material and the ions, and a large number of active sites can specifically recognize metal ions. However, MOFs materials have poor conductivity, and the coordination bonds between metals and organic ligands are easily degraded under external stimulation. These shortcomings limit their application in electrochemical sensors. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art or related art.

[0005] To this end, the first aspect of the present invention provides a ferrocene functionalized metal organic framework material, the preparation method of which comprises:

[0006] The method comprises dissolving ferrocenecarboxylic acid in a 2-morpholineethanesulfonic acid buffer solution, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, stirring, adjusting the pH value of the solution to 6.7-7.4, adding a dispersion of a metal organic framework NH2-MIL-53(Al), stirring and condensing at 20-30°C for 20-30h, and obtaining a ferrocene functionalized metal organic framework material Fc-NH2-MIL-53(Al) after centrifugation, washing and drying. The Fc-NH2-MIL-53(Al) material consists only of C, N, O, Al and Fe, and is a cluster structure formed in the form of sheets.

[0007] Furthermore, the mass ratio of ferrocenecarboxylic acid to the metal organic framework NH2-MIL-53(Al) is 5:6 to 5:4; the molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to N-hydroxysuccinimide is 1:1 to 1.3:1.

[0008] Furthermore, the metal organic framework NH2-MIL-53(Al) is prepared by a method comprising:

[0009] dissolving aluminum nitrate nonahydrate in deionized water to obtain an aluminum nitrate nonahydrate solution;

[0010] Dissolving 2-aminoterephthalic acid in N,N-dimethylformamide to obtain a 2-aminoterephthalic acid solution;

[0011] The aluminum nitrate nonahydrate solution and the 2-aminoterephthalic acid solution are mixed and stirred, and then kept at 145° C. to 155° C. for 20 to 30 hours, and the metal organic framework NH2-MIL-53(Al) is obtained by centrifugation, washing and drying;

[0012] The molar ratio of aluminum nitrate nonahydrate to 2-aminoterephthalic acid is 5:6 to 5:4.

[0013] A second aspect of the present invention provides an electrochemical sensor, comprising a working electrode of the electrochemical sensor, wherein the working electrode of the electrochemical sensor is modified with the above-mentioned ferrocene-functionalized metal-organic framework material.

[0014] Wherein, the working electrode of the Fc-NH2-MIL-53(Al) modified electrochemical sensor is prepared by:

[0015] Polishing the working electrode surface of the electrochemical sensor in order of decreasing particle size of the Al2O3 slurry until the electrode surface has a mirror effect;

[0016] Ultrasonic cleaning is performed on the polished working electrode of the electrochemical sensor, and then the electrode is dried in a protective atmosphere;

[0017] Evenly drop-coat the dried working electrode surface of the electrochemical sensor with a perfluorosulfonic acid resin dispersion of Fc-NH2-MIL-53 (Al) and allow to air dry naturally;

[0018] Wherein, the working electrode of the electrochemical sensor is a glassy carbon electrode.

[0019] Furthermore, the mass concentration of the Al2O3 slurry is 50g / L to 100g / L, wherein the Al2O3 particle size ranges from 30nm to 3μm; in the perfluorosulfonic acid resin dispersion of Fc-NH2-MIL-53(Al), the mass volume ratio of Fc-NH2-MIL-53(Al) to the perfluorosulfonic acid resin aqueous solution is 0.5 to 1.5:1 in mg / mL, and the drip coating amount is 0.5μL / mm 2 ~2.5μL / mm 2 .

[0020] A third aspect of the present invention provides an application of an electrochemical sensor, wherein the electrochemical sensor is used for detecting heavy metal lead.

[0021] Furthermore, the application method includes:

[0022] Establishing a standard curve: adding a lead standard solution to the electrolyte according to a lead ion concentration gradient range of 0 μg / L to 80 μg / L in the electrolyte, controlling the pH value of the electrolyte containing the lead standard solution to be 3.5 to 5.5, and using the electrochemical sensor to establish a lead ion concentration and peak current standard curve using square wave anodic stripping voltammetry;

[0023] Detection of lead ion content in the lead-containing solution to be tested: adding the lead-containing solution to be tested into an electrolytic cell, adding an electrolyte, adjusting the pH value of the electrolyte containing the lead-containing solution to be tested to 3.5-5.5, and using the electrochemical sensor to detect the lead ion content in the lead-containing solution to be tested by square wave anodic stripping voltammetry.

[0024] Furthermore, the electrolyte is an acetic acid-sodium acetate aqueous solution, the mixed concentration of the acetic acid-sodium acetate aqueous solution is 0.05 mol / L to 0.15 mol / L, and the pH value is 4.5 to 6.5;

[0025] The concentration of the lead standard solution is 1-80 μg / mL, and the volume ratio of the electrolyte to the lead standard solution is 50 mL: 2 μL-100 μL;

[0026] The volume ratio of the electrolyte to the lead-containing solution to be tested is 50 mL: 2 μL to 100 μL;

[0027] The detection parameters of the square wave anodic stripping voltammetry method are as follows: enrichment potential is: -0.9V to -1.3V, enrichment time is: 120s to 360s, standing time is: 5s to 15s, starting potential is: -1.3V to -1.0V, ending potential is: 0.4V to 0.6V, square wave amplitude is: 0.02V to 0.03V, potential increment is: 0.002V to 0.005V, and square wave frequency is: 15Hz to 35Hz.

[0028] Furthermore, the electrochemical sensor is used for the detection of heavy metal lead, wherein the detection concentration range of lead ions is 0.5 μg / L to 270 μg / L, the detection limit of lead ions is as low as 0.437 μg / L, and the sensitivity is 0.317 μA / (μg / L);

[0029] When the lead ion concentration in the lead-containing solution to be tested is not within the detection concentration range, the lead ion concentration is adjusted to be within the detection concentration range by concentrating, diluting or adding dropwise to a buffer solution.

[0030] Compared with the prior art, the present invention has at least the following beneficial effects:

[0031] The ferrocene functionalized metal organic framework material provided by the present invention is a Fc-NH2-MIL-53(Al) material formed by coupling NH2-MIL-53(Al) with ferrocenecarboxylic acid through 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide. The prepared Fc-NH2-MIL-53(Al) material is composed of only C, N, O, Al and Fe, and is a cluster structure formed by flakes. Fc-NH2-MIL-53(Al) is modified on the working electrode of an electrochemical sensor for specific detection of lead ions, showing the advantages of high sensitivity and low detection limit, and the preparation process is simple and the cost is low, and it has significant prospects for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1The morphology structure and mapping diagram of the Fc-NH2-MIL-53 (Al) material provided in Example 1 of the present invention. Among them, (a) is a high-resolution transmission electron microscope (HRTEM) image of Fc-NH2-MIL-53 (Al) at a magnification of 100nm; (b) a high-angle annular dark field (HAADF) image of Fc-NH2-MIL-53 (Al); (c) to (g) elemental maps of O, N, C, Al and Fe drawn using electron energy loss spectroscopy (EELS).

[0034] Figure 2 In the 0.1 mol / L acetic acid-sodium acetate aqueous solution (pH=4.5), the Fc-NH2-MIL-53 (Al) modified electrode provided in Example 2 of the present invention reacts with different concentrations of Pb 2+ Response curve and working curve of square wave anodic stripping voltammetry (1~80μg / L). DETAILED DESCRIPTION

[0035] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] In a first aspect of an embodiment of the present invention, a ferrocene-functionalized metal organic framework material is provided, wherein a preparation method thereof comprises:

[0037] Ferrocenecarboxylic acid is dissolved in 2-morpholineethanesulfonic acid buffer solution, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide are added, stirred, and then the pH value of the solution is adjusted to 6.7-7.4, and a dispersion of the metal organic framework NH2-MIL-53(Al) is added, and condensed at 20-30°C with stirring for 20-30h. After centrifugation, washing and drying, a ferrocene-functionalized metal organic framework material Fc-NH2-MIL-53(Al) is obtained.

[0038] Among them, the mass ratio of ferrocenecarboxylic acid to the metal organic framework NH2-MIL-53(Al) is 5:6 to 5:4; the molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to N-hydroxysuccinimide is 1:1 to 1.3:1.

[0039] Optionally, the metal organic framework NH2-MIL-53(Al), the preparation method comprises:

[0040] dissolving aluminum nitrate nonahydrate in deionized water to obtain an aluminum nitrate nonahydrate solution;

[0041] Dissolving 2-aminoterephthalic acid in N,N-dimethylformamide to obtain a 2-aminoterephthalic acid solution;

[0042] A nonahydrate aluminum nitrate solution and a 2-aminoterephthalic acid solution are mixed and stirred, followed by a hydrothermal reaction, and kept warm at 145° C. to 155° C. for 20 to 30 hours. The metal organic framework NH2-MIL-53 (Al) is obtained by centrifugal washing and drying; wherein the molar ratio of nonahydrate aluminum nitrate to 2-aminoterephthalic acid is 5:6 to 5:4.

[0043] The invention uses a solvent thermal method to react aluminum nitrate and 2-aminoterephthalic acid to generate an NH2-MIL-53 metal organic framework, and then couples the NH2-MIL-53 with ferrocenecarboxylic acid through 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide to form an Fc-NH2-MIL-53 (Al) material. The prepared Fc-NH2-MIL-53 (Al) material consists only of C, N, O, Al and Fe, and has a cluster structure formed in sheets.

[0044] The second aspect of the present invention provides an electrochemical sensor, comprising: a working electrode of the electrochemical sensor modified with the above-mentioned ferrocene-functionalized metal organic framework material Fc-NH2-MIL-53(Al).

[0045] Optionally, the working electrode of the electrochemical sensor is a glassy carbon electrode modified with a ferrocene-functionalized metal organic framework material Fc-NH2-MIL-53 (Al), Ag / AgCl is used as a reference electrode, and a Pt wire is used as a counter electrode. When used for heavy metal lead ion content detection, the heavy metal lead ion content of the solution in the electrolytic cell is detected by square wave anodic stripping voltammetry under stirring conditions.

[0046] In some embodiments, the working electrode of the modified electrochemical sensor is prepared by a method comprising:

[0047] The Al2O3 slurry is polished on the surface of the working electrode of the electrochemical sensor in descending order of particle size until the electrode surface presents a mirror effect; optionally, the mass concentration of the Al2O3 slurry is 50g / L~100g / L, preferably 70g / L~90g / L, wherein the Al2O3 particle size range is 30nm~3μm; optionally, the working electrode of the electrochemical sensor is a glassy carbon electrode, and the specific operation is to first polish the surface of the glassy carbon electrode with Al2O3 slurry with a particle size of 1μm~3μm for 180~220 times, and then polish the surface of the glassy carbon electrode with Al2O3 slurry with a particle size of 30nm~100nm for 180~220 times.

[0048] The polished working electrode of the electrochemical sensor is ultrasonically cleaned and then blown dry in a protective atmosphere; optionally, the working electrode of the electrochemical sensor is a glassy carbon electrode, and the polished glassy carbon electrode is ultrasonically cleaned in water and anhydrous ethanol successively, the frequency of ultrasonic cleaning is 30kHz to 50kHz, the power is 80W to 120W, and the time is 10s to 15s respectively; the protective atmosphere includes nitrogen or argon, and the protective atmosphere is a high-purity atmosphere with a purity of ≥99.9%.

[0049] The dried glassy carbon electrode surface is evenly coated with a perfluorosulfonic acid resin dispersion of a ferrocene-functionalized metal organic framework material and allowed to air dry naturally; optionally, in the perfluorosulfonic acid resin dispersion of the ferrocene-functionalized metal organic framework material, the mass volume ratio of Fc-NH2-MIL-53(Al) to the perfluorosulfonic acid resin aqueous solution is 0.5-1.5:1 in mg / mL, and in the perfluorosulfonic acid resin aqueous solution, the volume ratio of the perfluorosulfonic acid resin to water is 1:8-10, and the coating amount is 0.5 μL / mm 2 ~2.5μL / mm 2 The preparation method of the perfluorosulfonic acid resin dispersion of Fc-NH2-MIL-53(Al) is as follows: adding Fc-NH2-MIL-53(Al) to a perfluorosulfonic acid resin aqueous solution and dispersing the dispersion by ultrasonication; wherein the mass volume ratio of Fc-NH2-MIL-53(Al) to the perfluorosulfonic acid resin aqueous solution is 0.5-1.5:1 in mg / mL, the frequency of ultrasonic dispersion is 30kHz-50kHz, the power is 150W-300W, and the time is 10min-30min.

[0050] A third aspect of the present invention provides an application of an electrochemical sensor, wherein the electrochemical sensor is used for the detection of heavy metal lead, including the detection of heavy metal lead in electronic cigarette samples, the detection of heavy metal lead in natural water bodies, and the like.

[0051] The present invention integrates Fc-NH2-MIL-53(Al) into an electrochemical sensor and realizes the detection of Pb in actual samples by square wave anodic stripping voltammetry. 2+ The sensor has a wide linear range and a detection limit as low as 0.437 μg / L. Actual samples of electronic cigarette digestion liquid were analyzed to simulate the working environment of the sensor. The results show that the sensor achieves efficient and repeatable Pb 2+ In addition, the sensor of the present invention also showed a higher sensitivity of 0.317μA / (μg / L) than the prior art, and showed good conductivity, repeatability, reproducibility and stability during the test process. Based on the excellent performance of low cost, accurate measurement and convenient operation of the sensor, it is confirmed that the nanomaterial based on ferrocene functionalized metal organic framework is effective in detecting trace amounts of Pb 2+There is huge potential in this area.

[0052] The modified electrode obtained by the present invention has good electrochemical activity and conductivity, thus has a wide detection range, high sensitivity, low background current and high selectivity; the Fc-NH2-MIL-53 (Al) modified electrode used in the present invention to detect heavy metals has the characteristics of stability, anti-interference and high accuracy, especially for Pb 2+ It has good electrochemical response, showing the advantages of high sensitivity, low background current, high selectivity, etc. The detection limit is as low as 0.437 μg / L, indicating that the use of Fc-NH2-MIL-53 (Al) modified electrode for the detection of heavy metals provides a new path for the rapid detection of trace heavy metal ions in water environment.

[0053] In some embodiments, the electrochemical sensor is used to detect heavy metal lead, and the method includes:

[0054] Establishing a standard curve: adding a lead standard solution to an electrolyte in a lead ion concentration gradient range of 0 μg / L to 80 μg / L, controlling the pH value of the electrolyte containing the lead standard solution to be 3.5 to 5.5, preferably 4 to 5, and most preferably 4.5, using an electrochemical sensor and square wave anodic stripping voltammetry to establish a standard curve of lead ion concentration and peak current;

[0055] Detection of lead ion content in the lead-containing solution to be tested: Add the lead-containing solution to be tested into an electrolytic cell, add an electrolyte, adjust the pH value of the electrolyte containing the lead-containing solution to be tested to 3.5-5.5, preferably the pH value is 4-5, and most preferably the pH value is 4.5, and use an electrochemical sensor to detect the lead ion content in the lead-containing solution to be tested by square wave anodic stripping voltammetry.

[0056] It is understandable that determining the appropriate pH is the key to the test. If the pH is too low (below 3.5), more H + Ionized with Pb 2+ Coexistence; heavy metal ions on the electrode surface are easily dissolved. If the pH value is too high (above 5.5), OH - In solution, it is easy to react with Pb 2+ The metal hydroxide is precipitated and the peak current decreases. Therefore, during the test, the pH value of the solution in the electrolytic cell is controlled to be 3.5-5.5, preferably 4-5, and most preferably 4.5.

[0057] The electrolyte is an acetic acid-sodium acetate aqueous solution, the mixed concentration of the acetic acid-sodium acetate aqueous solution is 0.05 mol / L to 0.15 mol / L, and the pH value is 4.5 to 6.5; the electrolyte has the following two functions: 1) as a conductive medium, transmitting current; 2) carrying out electrochemical reactions under the action of the electric field, so that the anode dissolution can proceed smoothly and in a controlled manner.

[0058] The concentration of the lead standard solution is 1 to 80 μg / mL, and the volume ratio of the electrolyte to the lead standard solution is 50 mL: 2 μL to 100 μL;

[0059] The volume ratio of electrolyte to the lead solution to be tested is 50mL:2μL~100μL; the pH value of weak acid or neutral lead sample solution is generally 4.5~8.0. Weak acid or neutral heavy metal ion sample solution includes natural water, etc. The pH value of acidic lead sample solution is less than 4.5, and acidic heavy metal ion sample solution includes digestion solution, etc. The volume ratio of electrolyte to acidic lead sample solution is 50mL:2μL~100μL, and the pH value is adjusted to 3.5~5.5 with 5mol / L~10mol / L sodium hydroxide.

[0060] Square wave anodic stripping voltammetry, detection parameters are: enrichment potential: -0.9V~-1.3V, enrichment time: 120s~360s, standing time: 5s~15s, starting potential: -1.3V~-1.0V, ending potential: 0.4V~0.6V, square wave amplitude: 0.02V~0.03V, potential increment: 0.002V~0.005V, square wave frequency: 15Hz~35Hz.

[0061] In summary, the Fc-NH2-MIL-53(Al) modified electrode has the characteristics of stability, anti-interference and high accuracy in detecting heavy metals, especially for Pb 2+ It has good electrochemical response, showing advantages such as high sensitivity, low background current, and high selectivity, with a detection limit as low as 0.437μg / L, indicating that the use of Fc-NH2-MIL-53(Al) modified electrode for the detection of heavy metals provides a new path for the rapid detection of trace heavy metal ions in water environments. Specifically, the Fc-NH2-MIL-53(Al) modified electrode is used for the detection of heavy metal lead, with a lead ion detection concentration range of 0.5μg / L to 270μg / L, a lead ion detection limit as low as 0.437μg / L, and a sensitivity of 0.317μA / (μg / L); when the lead ion concentration in the lead-containing solution to be tested is not within the detection concentration range, its concentration is adjusted to the detection concentration range by concentration, dilution, or dropwise addition to a buffer solution.

[0062] Example 1 A ferrocene functionalized metal organic framework material

[0063] (I) A ferrocene functionalized metal organic framework material, the preparation method comprising the following steps:

[0064] (1) Preparation of NH2-MIL-53(Al)

[0065] 1.126 g of AlNO3.9H2O (3.1 mmol) and 0.56 g of 2-aminoterephthalic acid (3.1 mmol) were dissolved in 20 mL of deionized water and 10 mL of N,N-dimethylformamide, respectively, and then the two solutions were mixed, stirred for 15 minutes, and ultrasonicated for 15 minutes to obtain a mixed solution.

[0066] The mixed solution was transferred to a 100 ml Teflon-lined stainless steel autoclave, kept in an oven at 150°C for 24 h, naturally cooled to room temperature, centrifuged at 10,000 rpm for 5 min, and then the resulting product was further washed alternately with anhydrous ethanol and water for 3 times, and dried in a vacuum oven at 60°C for 12 h to obtain NH2-MIL-53(Al).

[0067] (2) Preparation of Fc-NH2-MIL-53(Al)

[0068] 30 mg of NH2-MIL-53 was ultrasonically dispersed in 4 ml of deionized water (solution A).

[0069] Dissolve 30 mg of ferrocenecarboxylic acid in 6 ml of 2-morpholineethanesulfonic acid buffer solution, then add 76.7 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 11.5 mg of N-hydroxysuccinimide, stir for half an hour to activate the carboxyl group, and then adjust the pH value of the solution to 7.2, add solution A, and stir at room temperature for 24 hours.

[0070] The mixture was then centrifuged and washed, and the remaining solid was then immersed in pure water for 24 hours, with the solvent replaced every 6 hours to remove unreacted ferrocenecarboxylic acid. Finally, the product was placed in a vacuum drying oven at 60° C. to obtain Fc-NH2-MIL-53(Al).

[0071] (II) Characterization of Fc-NH2-MIL-53(Al) materials

[0072] HRTEM analysis showed that Fc-NH2-MIL-53(Al) was a nanoscale sheet structure ( Figure 1 a). After ferrocene carboxylic acid is covalently linked to NH2-MIL-53(Al), many flake-like clusters are formed. Further analysis at the atomic level using elemental mapping and high-angle annular dark field (HAADF) ( Figure 1 b~ Figure 1g), indicating that the distribution of C, N, O, Al, and Fe of Fc-NH2-MIL-53(Al) matches well with the dispersion of the composite material, which indicates that ferrocenecarboxylic acid is successfully modified on the MOF framework.

[0073] Example 2 Application of Fc-NH2-MIL-53(Al) prepared in Example 1

[0074] (I) Preparation of Fc-NH2-MIL-53(Al) modified electrode

[0075] (1) The Al2O3 slurry is polished in descending order of particle size on the surface of the glassy carbon electrode until the electrode surface has a mirror effect;

[0076] (2) ultrasonically cleaning the glassy carbon electrode polished in step (1) in water and then in anhydrous ethanol, and then drying it in a protective atmosphere;

[0077] (3) Evenly drop-coat the surface of the glassy carbon electrode dried in step (2) with a perfluorosulfonic acid resin dispersion of Fc-NH2-MIL-53(Al), and allow to air dry naturally to obtain a Fc-NH2-MIL-53(Al) modified electrode.

[0078] (II) Establishment of standard curve for heavy metal lead detection

[0079] (1) The lead standard solution was added dropwise to 50 mL of acetic acid-sodium acetate aqueous solution (0.1 mol / L, pH 4.5) in the electrolytic cell, so that after each addition, the Pb content of the solution in the electrolytic cell 2+ The concentrations were: 0μg / L, 1μg / L, 2μg / L, 4μg / L, 5μg / L, 10μg / L, 15μg / L, 20μg / L, 30μg / L, 50μg / L, 80μg / L, and then, the Fc-NH2-MIL-53(Al) modified electrode was used as the working electrode, Ag / AgCl (the internal solution was a saturated KCl solution) as the reference electrode, and Pt wire as the counter electrode, which were connected to the electrochemical workstation RST5000.

[0080] (2) Under stirring conditions at a speed of 300 r / min, square wave anodic stripping voltammetry was used to detect the Pb 2+ Content (detection parameters: enrichment potential: -1.2V, enrichment time: 360s, standing time: 10s, starting potential: -1.2V, ending potential: 0.6V, square wave amplitude: 0.025V, potential increment: 0.004V, square wave frequency: 25Hz).

[0081] like Figure 2 As shown in a, Pb 2+The response curve of square wave anodic stripping voltammetry (1-80 μg / L) shows that as Pb 2 + As the concentration increases, the dissolution peak current gradually increases, the dissolution peak potential gradually shifts positively, and peak separation occurs when a certain concentration is reached. This is a normal phenomenon, which may be caused by the specific interaction between the modified film and the analyte and will not affect the detection of heavy metal ions. Figure 2 From the concentration curve, it can be seen that the Fc-NH2-MIL-53(Al) modified electrode has an extremely low background current (as low as 0.26μA), which is conducive to the detection of target ion dissolution and obtains an extremely low detection limit (LOD). Figure 2 As shown in b, Pb 2+ In the concentration range (1-80 μg / L), the formula: LOD = 3Sb / S is used to calculate the detection limit LOD = 0.437 μg / L (S / N = 3). The calculated LOD is much lower than the recommended value for drinking water given by WHO (10 μg / L). Through calculation, the linear relationship corresponding to the Fc-NH2-MIL-53 (Al) modified electrode is expressed as follows:

[0082] 1 to 80 μg / L: I p (μA) = 0.317x + 0.122, R 2 =0.999.

[0083] The above concentration range is for different concentrations of Pb adsorbed on the Fc-NH2-MIL-53(Al) modified electrode. 2+ , redox behavior occurs through adsorption, the reaction rate is different at different concentrations, and different calibration curves are selected for calculation. Therefore, the Fc-NH2-MIL-53(Al) modified electrode performs well in the electrochemical detection of heavy metal ions.

[0084] (III) Detection of heavy metal lead using Fc-NH2-MIL-53(Al) modified electrode (actual sample detection)

[0085] In addition to quantitatively analyzing the water sample according to Example 1 of the method for detecting heavy metals using Fc-NH2-MIL-53 (Al) modified electrodes, an inductively coupled plasma mass spectrometer (ICP-MS) was used as a verification method to detect electronic cigarettes. Pb (II) in the electronic cigarette digestion solution was detected, and the electronic cigarette liquid was digested. The preparation of the electronic cigarette digestion solution first weighed 0.3-0.4g of the electronic cigarette liquid and placed it in a polytetrafluoroethylene tank. At the same time, a blank sample was prepared by adding 5mL nitric acid and 2mL hydrogen peroxide. The digestion program set according to the microwave digestion conditions in the standard was followed by a program temperature increase reaction. Take out the digestion tube, transfer the digestion solution to a 50mL reagent bottle, wash the inner tank with water 3 times, combine the washing solution and adjust the volume to the scale, and after mixing, test it on the machine according to the instrument conditions of GB5009.11-2014. Among them, the electronic cigarette modified electrode detection method is to take the electronic cigarette digestion solution in this example and dilute it 250 times with 0.1 mol / L HAc-NaAc for detection. The detection results are shown in Table 1.

[0086] Table 1 Detection of Pb in electronic cigarette digestion solution by Fc-NH2-MIL-53(Al) modified electrode 2+ Content and ICP-MS test results

[0087]

[0088] Note: The calculation formula of recovery rate in the table is (three parallel measurements of Pb 2+ Average content) / Pb 2+ concentration.

[0089] As shown in Table 1, it can be found that the sensor made by Fc-NH2-MIL-53(Al) modified electrode has a good 2+ The recoveries were 98.11% and 95.67% respectively, with an error of less than 5%. ICP-MS was used to verify the results, and the error was small, indicating that the sensor can accurately and efficiently detect heavy metal lead in complex e-cigarette samples and has good application prospects.

[0090] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.

Claims

1. A ferrocene functionalized metal organic framework material, characterized in that: The preparation method thereof comprises: The method comprises dissolving ferrocenecarboxylic acid in a 2-morpholineethanesulfonic acid buffer solution, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, stirring, adjusting the pH value of the solution to 6.7-7.4, adding a dispersion of a metal organic framework NH2-MIL-53(Al), stirring and condensing at 20-30°C for 20-30h, and obtaining a ferrocene functionalized metal organic framework material Fc-NH2-MIL-53(Al) after centrifugation, washing and drying. The Fc-NH2-MIL-53(Al) material consists only of C, N, O, Al and Fe, and is a cluster structure formed in the form of sheets.

2. The ferrocene functionalized metal organic framework material according to claim 1, characterized in that The mass ratio of ferrocenecarboxylic acid to the metal organic framework NH2-MIL-53(Al) is 5:6 to 5:4; The molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to N-hydroxysuccinimide is 1:1 to 1.3:

1.

3. The ferrocene functionalized metal organic framework material according to claim 1 or 2, characterized in that The metal organic framework NH2-MIL-53(Al) is prepared by: dissolving aluminum nitrate nonahydrate in deionized water to obtain an aluminum nitrate nonahydrate solution; Dissolving 2-aminoterephthalic acid in N,N-dimethylformamide to obtain a 2-aminoterephthalic acid solution; The aluminum nitrate nonahydrate solution and the 2-aminoterephthalic acid solution are mixed and stirred, and then kept at 145° C. to 155° C. for 20 to 30 hours, and the metal organic framework NH2-MIL-53(Al) is obtained by centrifugation, washing and drying; The molar ratio of aluminum nitrate nonahydrate to 2-aminoterephthalic acid is 5:6 to 5:

4.

4. An electrochemical sensor, characterized in that The invention comprises a working electrode of an electrochemical sensor, wherein the working electrode of the electrochemical sensor is modified by the ferrocene functionalized metal organic framework material according to any one of claims 1 to 3.

5. The electrochemical sensor according to claim 4, characterized in that The working electrode of the Fc-NH2-MIL-53(Al) modified electrochemical sensor is prepared by: Polishing the working electrode surface of the electrochemical sensor in order of decreasing particle size of the Al2O3 slurry until the electrode surface has a mirror effect; Ultrasonic cleaning is performed on the polished working electrode of the electrochemical sensor, and then the electrode is dried in a protective atmosphere; Evenly drop-coat the dried working electrode surface of the electrochemical sensor with a perfluorosulfonic acid resin dispersion of Fc-NH2-MIL-53 (Al) and allow to air dry naturally; Wherein, the working electrode of the electrochemical sensor is a glassy carbon electrode.

6. The electrochemical sensor according to claim 5, characterized in that The mass concentration of the Al2O3 slurry is 50g / L to 100g / L, wherein the Al2O3 particle size ranges from 30nm to 3μm; In the perfluorosulfonic acid resin dispersion of Fc-NH2-MIL-53(Al), the mass volume ratio of Fc-NH2-MIL-53(Al) to the perfluorosulfonic acid resin aqueous solution is 0.5-1.5:1 in mg / mL, and the drop coating amount is 0.5 μL / mm 2 ~2.5μL / mm 2 .

7. An application of an electrochemical sensor, characterized in that: The electrochemical sensor according to any one of claims 4 to 6 is used for detecting heavy metal lead.

8. Use according to claim 7, characterized in that Application methods include: Establishing a standard curve: adding a lead standard solution to the electrolyte according to a lead ion concentration gradient range of 0 μg / L to 80 μg / L in the electrolyte, controlling the pH value of the electrolyte containing the lead standard solution to be 3.5 to 5.5, and using the electrochemical sensor to establish a lead ion concentration and peak current standard curve using square wave anodic stripping voltammetry; Detection of lead ion content in the lead-containing solution to be tested: adding the lead-containing solution to be tested into an electrolytic cell, adding an electrolyte, adjusting the pH value of the electrolyte containing the lead-containing solution to be tested to 3.5-5.5, and using the electrochemical sensor to detect the lead ion content in the lead-containing solution to be tested by square wave anodic stripping voltammetry.

9. The use according to claim 8, characterized in that The electrolyte is an acetic acid-sodium acetate aqueous solution, the mixed concentration of the acetic acid-sodium acetate aqueous solution is 0.05mol / L to 0.15mol / L, and the pH value is 4.5 to 6.5; The concentration of the lead standard solution is 1-80 μg / mL, and the volume ratio of the electrolyte to the lead standard solution is 50 mL: 2 μL-100 μL; The volume ratio of the electrolyte to the lead-containing solution to be tested is 50 mL: 2 μL to 100 μL; The detection parameters of the square wave anodic stripping voltammetry method are as follows: enrichment potential is: -0.9V to -1.3V, enrichment time is: 120s to 360s, standing time is: 5s to 15s, starting potential is: -1.3V to -1.0V, ending potential is: 0.4V to 0.6V, square wave amplitude is: 0.02V to 0.03V, potential increment is: 0.002V to 0.005V, and square wave frequency is: 15Hz to 35Hz.

10. The use according to claim 9, characterized in that The electrochemical sensor is used for the detection of heavy metal lead, wherein the detection concentration range of lead ions is 0.5 μg / L to 270 μg / L, the detection limit of lead ions is as low as 0.437 μg / L, and the sensitivity is 0.317 μA / (μg / L); When the lead ion concentration in the lead-containing solution to be tested is not within the detection concentration range, the lead ion concentration is adjusted to be within the detection concentration range by concentrating, diluting or adding dropwise to a buffer solution.